Prevalent infection of Paragonimus larvae in Yen Bai province - Doanh, Pham Ngoc; Le, Nguyen Thi; Minh, Nguyen Thi; Ha, Nguyen Van (Academia Journal of Biology, 2014)
An investigation for the Paragonimus larvae infection was conducted in 12 villages of 8 districts belonging to the Yenbai province in 2005. Paragonimus metacercariae were found in 3 villages: Khanhhoa, Anlac (Lucyen district) and Ngoia (Vanyen district). Only one mountainous crab species Potamiscus tannanti Rathbun served as the second intermediate host of Paragonimus in study sites. The infective prevalence of Paragonimus metacercaria in crabs were quite high: the infection rate and density in the Khanhhoa village were 53.3% and 1-82 metacercaria/crab (average 28.8) respectively, in the Anlac village: 50% and 1-51 metacercaria/crab (average 19.2) and in the Ngoia village: 36.9% and 1-31 metacercaria/crab (average 14.2). The crabs P. tannanti in the Khanhhoa and Ngoia villages were infected with only metacercaria of P. heterotremus while this crab species in the Anlac village were concurrently infected with those of P. heterotremus and Paragonimus sp.. The infection of metacercaria of earlier species was higher than that of latter species. Only one snail species Pseudotricula sp. served as the first intermediate host of Paragonimus in the Yenbai province. The cercaria of Paragonimus was found at 0.5% of this snail in the Khanhhoa village, but not yet found in Anlac and the Ngoia villages.